Is sarcopenia a missed factor in the management of patients with metastatic breast cancer?. (February 2022) - Deluche, Elise; Lachatre, Denis; Di Palma, Mario; Simon, Hélène; Tissot, Valentin; Vansteene, Damien; Meingan, Philippe; Mohebi, Alexis; Lenczner, Grégory; Pigneur, Francois; Goldwasser, Francois; Raynard, Bruno; et al.
Abstract: Background: Sarcopenia has emerged as an important parameter to predict outcomes and treatment toxicity. However, limited data are available to assess sarcopenia prevalence in metastatic breast cancer and to evaluate its management. Methods: The SCAN study was a cross-sectional multicenter French study that aimed to estimate sarcopenia prevalence in a real-life sample of metastatic cancer patients. Sarcopenia was identified by low muscle mass (estimated from the skeletal muscle index at the third lumbar, via computed tomography) and low muscle strength (defined by handgrip strength). Three populations were distinguished based on EWGSOP criteria: a sarcopenic group with low muscle mass AND strength, a pre-sarcopenic group with low muscle mass OR strength and a normal group with high muscle mass AND strength. Results: Among 766 included patients, 139 patients with breast cancer and median age of 61.2 years (29.9–97.8 years) were evaluable; 29.5% were sarcopenic and 41.0% were pre-sarcopenic. Sarcopenic patients were older ( P  < 0.01), had a worse PS-score ( P  < 0.05), and a higher number of metastatic sites ( P  < 0.01), the majority being hepatic and bone. A moderate agreement between the oncologist's diagnosis and sarcopenia evaluation by muscle mass and strength was recognized (Cohen's kappa = 0.45). No associations were found between sarcopenia and adverse event occurrence in the 12 patients for whom these were reported. Sarcopenic patients were underdiagnosed and nutritional care and physical activity were less proposed. Conclusion: It is necessary to evaluate sarcopenia due to its impact on patient prognosis, and its utility in guiding patient management in metastatic breast cancer. Highlights: Sarcopenia prevalence was 29.5% in metastatic breast cancer patients. Pre-sarcopenia was found in 41.0% of metastatic breast cancer patients. Anthropometric parameters or oncologist assessments do not fully assess sarcopenia. Sarcopenia is under-diagnosed in metastatic cancer. Sarcopenic patients are under-referred for nutritional management.